DIPLOMASI KOMERSIAL INDONESIA TERHADAP JEPANG DALAM MENDORONG EKSPOR UDANG BEKU: STUDI KASUS PERAN ITPC PERIODE 2018-2021 - Pradipta Anugra Firdausa (2023)
This research aims to identify and understand the commercial diplomacy executed by Indonesia Trade Promotion Center (ITPC) Osaka in order to promote exports of Frozen Shrimp to Japan during the 2018-2021 period. Shrimp is a leading commodity of Indonesian marine products which contributes more than 20% of Indonesia's GDP, while Japan is well-known as a world seafood market and is Indonesia's third largest strategic partner. The majority of Indonesian marine product exports to Japan are dominated by shrimp which are exported in frozen conditions or commonly called frozen shrimp. However, exports of frozen shrimp from Indonesia tend to fluctuate during the 2018-2021 period. This condition is inversely proportional to India and Vietnam which tend to experience an increase in volume. The author will use the concept of commercial diplomacy to analyse how commercial diplomats are represented by state actors, in this context the ITPC Osaka to encourage frozen shrimp exports to Japan during 2018-2021. It was found out that in order to promoting exports of frozen shrimp in Japan, ITPC carried out a series of activities such as making a Market Brief, promoting through exhibitions in Japan, Business Matching/Match Making, and solving problems. In 2021 frozen shrimp exports to Japan have increase compared to previous years.